Elucidating the genomic history of commercially used Bacillus thuringiensis subsp. tenebrionis strain NB176 - Schäfer, Lea; Volk, Frank; Kleespies, Regina G.; Jehle, Johannes A.; Wennmann, Jörg T. (Frontiers in Cellular and Infection Microbiology, 2023)
Bacillus thuringiensis subsp. tenebrionis (Btt) produces a coleopteran-specific crystal protoxin protein (Cry3Aa δ-endotoxin). After its discovery in 1982, the strain NB125 (DSM 5526) was eventually registered in 1990 to control the Colorado potato beetle (Leptinotarsa decemlineata). Gamma-irradiation of NB125 resulted in strain NB176-1 (DSM 5480) that exhibited higher cry3Aa production and became the active ingredient of the plant protection product Novodor® FC. Here, we report a comparative genome analysis of the parental strain NB125, its derivative NB176-1 and the current commercial production strain NB176. The entire genome sequences of the parental and derivative strains were deciphered by a hybrid de novo approach using short (Illumina) and long (Nanopore) read sequencing techniques. Genome assembly revealed a chromosome of 5.4 to 5.6 Mbp and six plasmids with a size range from 14.9 to 250.5 kbp for each strain. The major differences among the original NB125 and the derivative strains NB176-1 and NB176 were an additional copy of the cry3Aa gene, which translocated to another plasmid as well as a chromosomal deletion ( 178 kbp) in NB176. The assembled genome sequences were further analyzed in silico for the presence of virulence and antimicrobial resistance (AMR) genes.